CT of Multiple Sclerosis: Reassessment of Delayed Scanning with High Doses of Contrast Material - Spiegel, S. M.; Viñuela, Fernando; Fox, Allan J.; Pelz, David M. (American Journal of Neuroradiology, 1985)
A prospective study involving 87 patients was carried out to evaluate the necessity for a high dose of contrast material in addition to delayed computed tomographic (CT) scanning for optimal detection of the lesions of multiple sclerosis in the brain. In patients with either clinically definite multiple sclerosis or laboratory-supported definite multiple slerosis, CT scans were obtained with a uniform protocol. Lesions consistent with multiple sclerosis were demonstrated on the second scan in 54 patients. In 36 of these 54 patients, the high-dose delayed scan added information. These results are quite similar to those of a previous study from this institution using different patients, in whom the second scan was obtained immediately after the bolus injection of contrast material containing 40 g of organically bound iodine. The lack of real difference in the results of the two studies indicates that the increased dose, not just the delay in scanning, is necessary for a proper study.